Review on development and innovation of hydrogen-powered rail vehicles and power systems - LI Ming; GAO Lihua; LI Zeyu (机车电传动)
Developing hydrogen energy is a crucial step towards achieving the "carbon peaking and carbon neutrality" goals. This paper presented a systematic review on the current application status of hydrogen-powered rail vehicles and the key technologies at home and abroad, and summarized the technical difficulties associated with hydrogen-powered rail vehicles and their power systems, based on the operational characteristics of rail transit. To address the constraints arising due to conflicting factors such as space and weight, energy and efficiency, and operation/maintenance and cost, some innovative approaches in application research were proposed, such as the low cost and high quality design, high energy efficiency design, high safety and reliability design, and standard system promotion. The research presented in this paper can serve as a technical reference for the application of hydrogen energy in rail vehicles.